"A community system": A critical foundation for the epidemic prevention and control of SARS‐CoV‐2. (16th July 2020) - Zhang, Xiaoyan; Yang, Shiyu
Abstract: In response to COVID‐19 that has constituted a global pandemic, countries around the world have successively adopted a myriad of prevention and control measures. As the first country with the COVID‐19 outbreak, the Chinese government has adopted a series of timely and strict prevention and control measures against the spread of the SARS‐CoV‐2, which has effectively slowed down the spread of the SARS‐CoV‐2 and created a valuable window for the international community to overcome the epidemic. China's experience in combating the COVID‐19 has shown that building a community prevention and control system is essential to control the spread of coronavirus. As the backbone of the epidemic prevention and control system, the community prevention and control system plays an important role in improving the pattern of disorderly medical treatment, screening suspected patients, preventing the input of pathogens, ensuring residents' medical needs, stabilizing public sentiment, reducing disease fear, and maintaining residents' national security. At the same time, it also exposed the problems of the community prevention and control epidemic system in terms of infrastructure, human resources, and internal systems. Based on this, this article suggests that we should improve the hardware facilities of community, improve the internal mechanism of the community, strengthen the stability of the community talent team, improve the level of linkage between the community and other departments to prevent and control the spread of SARS‐CoV‐2, effectively use information technology and actively mobilize social forces to help community prevention and control COVID‐19.